1976
DOI: 10.3109/00498257609151612
|View full text |Cite
|
Sign up to set email alerts
|

Bile and Urine as Complementary Pathways for the Excretion of Foreign Organic Compounds

Abstract: 1. The urinary and biliary excretion in the rat of 30 aromatic compounds with mol. wt. of 100-850, and largely excreted unchanged, has been studied. 2. These compounds fall into three groups as regards their pattern of elimination, which is related to mol. wt: group 1, with mol. wt. less than 350 and the major route of elimination the urine. When urinary excretion is prevented by ligating the renal pedicles the biliary excretion remains low. group 2, with mol, wt. of 450-850 which are excreted predominantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…In the urinary excretion study, each Py-Im polyamide dissolved in distilled water was administered intravenously to the jugular vein of the rats at a dose of 2.0 mg/kg. Urine samples were collected after 1,3,5,8,12,24,36, and 48 h using metabolic cages after dosing. In the biliary excretion study, a cannula was inserted into the bile duct of the rats under anesthesia with pentobarbital sodium.…”
Section: Pharmacokinetic Modeling and Prediction Of Plasma Pyrrole-immentioning
confidence: 99%
“…In the urinary excretion study, each Py-Im polyamide dissolved in distilled water was administered intravenously to the jugular vein of the rats at a dose of 2.0 mg/kg. Urine samples were collected after 1,3,5,8,12,24,36, and 48 h using metabolic cages after dosing. In the biliary excretion study, a cannula was inserted into the bile duct of the rats under anesthesia with pentobarbital sodium.…”
Section: Pharmacokinetic Modeling and Prediction Of Plasma Pyrrole-immentioning
confidence: 99%
“…One approach is to relate the extent of biliary excretion of administered compounds to their molecular features. This approach has shown that certain physicochemical parameters (molecular weight, polarity, molecular structure) markedly influence the extent to which a compound is excreted into bile (Millburn et al, 1967;Hirom et al, 1972) and it has been suggested that it is possible to predict from the characteristics whether bile or urine will be the major excretory route for a particular compound (Hirom et al, 1976). However, it is clear that the biliary excretion of a compound is a multi-stage process and the passage of a choleophile from the hepatocyte into the bile is just one of them.…”
Section: Discussionmentioning
confidence: 99%
“…No peaks of metabolites were detected for all the samples. The differences in the molecular weights of compounds affect their eliminations (Hirom et al, 1976). The molecular weight thresholds for the excretion of organic cations into rat bile were found to be in the ranges of 200 ± 50 for monovalent organic cations and 500-600 for bivalent organic cations.…”
Section: Urinary and Biliary Excretionsmentioning
confidence: 99%